Pengaruh Penggunaan Media Audio Visual terhadap Hasil Belajar Ilmu Pengetahuan Sosial (IPS) pada Materi “Proklamasi” Kelas VIII di SMP Negeri 22 Semarang - Salma Tiyas Anggraini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The success of a lesson can be seen from the learning outcomes obtained by students have increased. In this study, researchers aimed to reveal the effect of using video-based audio-visual social studies learning media from the Youtube channel with proclamation material at SMPN 22 Semarang class VIII which was carried out using a quasi-experiment approach of pretest and posttest type of control class and experimental class whose test results obtained a Z value of -4,765 with a significance value (Asymp. Sig. 2-tailed) of <0.001 in the Wilcoxon Signed Rank Test pretest and posttest of the control class while in the experimental class test obtained a Z value of -5.004 with a significance value (Asymp. Sig. 2-tailed) of <0.001 and as many as 94.1% (32 students) increased the score of learning outcomes after the use of audio-visual media learning social studies proclamation material. The use of audio-visual media in social studies learning still raises obstacles in its implementation, such as the lack of availability of facilities and infrastructure, limited class hours, and the lack of teacher ability to operate technology.